2017
DOI: 10.1002/pbc.26774
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea prescription, availability and use for children with sickle cell disease in Italy: Results of a National Multicenter survey

Abstract: HU effectiveness is demonstrated in a national cohort of children with SCD living in Italy, even at a lower dose than recommended, revealing good adherence to a treatment program by a socially vulnerable group of patients such as immigrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 33 publications
4
31
0
1
Order By: Relevance
“…As expected, in contrast to SCA patients who did not receive HU, those who received this treatment presented increased HbF levels and improvements in hemolytic, hepatic and inflammatory profiles (hemoglobin, hematocrit, MCV, MCH, reticulocytes, MCHC, RDW, AST, total bilirubin, LDH, WBC, neutrophils, eosinophils, lymphocytes, monocytes, platelets, and plateletcrit). These findings corroborate previous studies, which also demonstrated improvements in hemolytic, hepatic and inflammatory profiles in patients with SCA undergoing HU therapy (de Souza Santos and Maia, 2010;Voskaridou et al, 2010;de Souza Torres et al, 2012;Pallis et al, 2014;Belini Junior et al, 2015;Shome et al, 2016;Quarmyne et al, 2017;Colombatti et al, 2018). We further observed an increase in HDL-C concentration, demonstrating the effect of HU on lipid metabolism, which is consistent with our previous results (Yahouedehou et al, 2018b;Yahouedehou et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…As expected, in contrast to SCA patients who did not receive HU, those who received this treatment presented increased HbF levels and improvements in hemolytic, hepatic and inflammatory profiles (hemoglobin, hematocrit, MCV, MCH, reticulocytes, MCHC, RDW, AST, total bilirubin, LDH, WBC, neutrophils, eosinophils, lymphocytes, monocytes, platelets, and plateletcrit). These findings corroborate previous studies, which also demonstrated improvements in hemolytic, hepatic and inflammatory profiles in patients with SCA undergoing HU therapy (de Souza Santos and Maia, 2010;Voskaridou et al, 2010;de Souza Torres et al, 2012;Pallis et al, 2014;Belini Junior et al, 2015;Shome et al, 2016;Quarmyne et al, 2017;Colombatti et al, 2018). We further observed an increase in HDL-C concentration, demonstrating the effect of HU on lipid metabolism, which is consistent with our previous results (Yahouedehou et al, 2018b;Yahouedehou et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…A large body of preclinical and clinical evidence has demonstrated that HU reduces the morbidity and mortality of both adults and children (including infants) with SCD, with a favorable tolerability profile and without significant short-term and long-term safety concerns [5668]. A series of real-life reports documenting the use of HU in Italy have recently been published [20, 22, 69]. HU was shown to be beneficial as a treatment option in a retrospective, nationwide cohort study of 1,638 patients with SCD of whom 652 patients had received HU during their disease course [20].…”
Section: Introductionmentioning
confidence: 99%
“…Follow‐up from the subjects enrolled in these trials showed salutary long‐term benefits in morbidity, mortality, laboratory tests and preservation of organ function (McGann & Ware, , ). Several studies conducted in Italy, Belgium and India have shown significant clinical benefits attributable to HC (Jain et al , ; Nottage et al , ; Le et al , ; Colombatti et al , ). However, these studies were limited with respect to the relatively small simple size, single institution design and shorter follow‐up periods in randomized clinical trials.…”
Section: Introductionmentioning
confidence: 99%